Implementasi Problem Based Learning Pada Tema Selamatkan Makhluk Hidup Untuk Meningkatkan Prestasi Belajar dan Keaktifan Siswa Kelas VI SDN Ngepeh - Mariyono Mariyono (UNIVERSITAS PGRI MADIUN, 2022)
The results of the initial observations at SDN Ngepeh found several findings, namely the lack of optimal student involvement in learning, so that students are passive. Students cannot find their own knowledge and skills. Theme 1 learning activities show less than optimal results. This is because the learning method applied does not involve active student participation because the method used is the question assignment method, without being given appropriate materials or media. One effort to improve students' cognitive abilities and student activity is to use learning methods that are appropriate to the material to be taught by the teacher. The purpose of this research is to find out if the implementation of the problem-based learning method can improve student learning achievement and the activity of class VI SDN Ngepeh for the 2022/2023 academic year. This research is a classroom action research conducted at SDN Ngepeh in two cycles. This type of research is qualitative and quantitative research. Data collection techniques using tests and student activity observation sheets.The results showed that the application of the Problem Based Learning method could improve the achievement of class VI students at SDN Ngepeh. The increase in student achievement from cycle I was 53% and cycle II was 86%. The increase in student achievement from cycle I to cycle II was 33%. The implementation of the Problem Based Learning method can increase the activity of class VI students at SDN Ngepeh. Increased student activity from cycle I by 40% and Cycle II by 93%. Increased learning activity from cycle I to cycle II by 53%.